2004
DOI: 10.1159/000076749
|View full text |Cite
|
Sign up to set email alerts
|

Tubular and Interstitial Cell Apoptosis in the Streptozotocin-Diabetic Rat Kidney

Abstract: Background/Aims: Angiotensin II (Ang II) mediates progressive nephron loss in diabetes and stimulates apoptotic cell death in several tissues. We studied the extent of apoptosis in streptozotocin (STZ) induced diabetic nephropathy in the rat and the effects of insulin and type 1 (AT1) or type 2 (AT2) Ang II receptor blockade with losartan or PD123319, respectively. Methods: Three groups of rats were studied after 2 and 12 weeks: (1) controls ; (2) STZ-diabetic rats (STZ rats), and (3) STZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
42
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 37 publications
11
42
0
2
Order By: Relevance
“…26 Kumar et al have shown that apoptotic cell death plays a role in the occurrence of kidney damage in diabetic nephropathy. 27 Wong et al reported that elevated blood glucose levels affect apoptosis-controlling genes. 28 We found that CASP1, IL1-alpha, BAD, DFFA, DFFB, CASP6 and DIABLO gene expression changes were significantly increased in diabetic rats compared to control rats.…”
Section: Discussionmentioning
confidence: 99%
“…26 Kumar et al have shown that apoptotic cell death plays a role in the occurrence of kidney damage in diabetic nephropathy. 27 Wong et al reported that elevated blood glucose levels affect apoptosis-controlling genes. 28 We found that CASP1, IL1-alpha, BAD, DFFA, DFFB, CASP6 and DIABLO gene expression changes were significantly increased in diabetic rats compared to control rats.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for a primary role of apoptosis in either human or experimental diabetic nephropathy is scant (51)(52)(53)(54). However, podocyte apoptosis can be demonstrated in cell culture.…”
Section: Podocyte Apoptosis And/or Detachment In Humans and Animal Momentioning
confidence: 99%
“…Long-term damage, dysfunction and failure of the kidneys are major complications of diabetes mellitus. Increased glucose levels in the blood have been shown to lead to oxidative stress, which is considered as one of the causative factors of diabetes-associated kidney disorders such as apoptosis, tubular atrophy and necrosis (Kumar et al 2004;El-Midaoui & de Champlain 2005). Administration of the GGCP extract or glibenclamide improved the architecture of the kidney and by extension restored its functionality.…”
Section: Indexmentioning
confidence: 99%